Homo sovieticus – „jednowymiarowy klient komunizmu”, czy „fenomen o wielu twarzach”? - Kania, Eliza (Wydawnictwo Naukowe WNPiD UAM, 2012)
The paper analyzes a symbolic notion that entered Polish political discourse at the time of political transformation, namely the notion of homo sovieticus. The author emphasizes a di- chotomy in how this notion has been presented in Poland and in the Soviet Union, and later in the Russian Federation. In Poland this symbol was primarily assigned all the negative features associated with the pre-transformation society and with soviet ‘communism’ (Rev. J. Tisch- ner). In Russia, the associations most frequently evoked by the notion of homo sovieticus were more varied (A. Zinovjev, S. Alieksiyewich, W. Yerofieyev). Ideological zeal, or commit- ment to the ethos of work, were referred to more often there. Czes3aw Milosz presented an- other interesting approach to the topic, interpreting homo sovieticus more in terms of a victim of the ‘totalitarian system’ while emphasizing the issue of violence – both symbolic and sub- jective, and the uniformization of society (which had a considerable impact on ‘shaping’ the social mass as desired by the authorities). The paper attempts to stress the fact that the notion of homo sovieticus or soviet man is fre- quently refused the right to an actual identity, as it is mainly associated with the negative as- pects of human nature. It is forgotten that an individual identity is the sum total of many factors: its self-identification and placement, the collective self-consciousness of the group, the historical conditions or axiological system prevailing and socially accepted in a given his- torical period.
Homo sovieticus – ‘a single-dimensional client of communism’ or a ‘multifaceted phenomenon’?
Keywords: homo sovieticus; dyskurs publiczny